Źródła przewagi konkurencyjnej przedsiębiorstw sfery agrobiznesu - Arend, Andrzej (The Sources of Competitive Advantage of Enterprises from Agribusiness Sphere, 2006)
Strong competitive position of an enterprise plays a very important role in market conditions. Among many factors having influence on market success of studied food-processing enterprises, quality and price - leading instruments of strengthening competitive position of these firms acquire special significance. The structure of instruments of competing is of a flexible character and it undergoes modifications influenced by changes of customers' preferences and changes in competitors' activities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 31-36